Comparative bioefficacy of Bacillus thuringiensis var. kurstaki and neem on American white moth, Hyphantria cunea Drury - Oftadeh, Marziyeh; Sendi, Jalal Jalali; Mutunga, James; Ebadollahi, Asgar (Journal of Plant Protection Research, 2026)
The American white moth, Hyphantria cunea Drury, is a polyphagous insect pest that feeds on a wide range of fruit and forest trees. In the present study, the potential of the most commonly used biological pesticide Bacillus thuringiensis var. kurstaki (Btk) and the botanical- -derived insecticide neem Achook® and their combination on the mortality and physiological disruptions of H. cunea was investigated. The LC30 (1.200 and 13.350 ppm for Bt and neem, respectively), LC50 (3.103 and 31.753 ppm for Bt and neem, respectively), and their combinations were considered in all biochemical assays. The combination of biopesticides showed a synergistic phenomenon in all treatments at different concentrations. To explore the underlying mechanisms, we assessed the main biochemical compounds, including the activity of digestive and detoxifying enzymes of the moth larvae. Significant reductions in the activities of protease, amylase, lipase, α-glucosidase, and β-glucosidase were realized compared to the control (p < 0.05). The activities of detoxifying enzymes, specifically α- and β-esterases, glutathione S-transferase, and phenol oxidase, exhibited significant increases in the treated groups. Conversely, the activity of acetylcholine esterase was found to be decreased across all treatment conditions. The treatments administered resulted in a statistically significant reduction in pupal weight (p < 0.05). The lowest average pupal weight was recorded for the combination of Bacillus thuringiensis (Bt) and neem at their concentration (LC50) of 98.98 mg. This research demonstrated that using Bt and neem had combined synergistic pesticidal effects that can be proposed for integrated pest management of H. cunea.